Новітні практики підготовки фахівців технічних спеціальностей у вищій школі: досвід Харківської області - Бабаєв, Володимир Миколайович (НТУ "ХПІ", 2010)
Стаття присвячена висвітленню питань, пов’язаних з підготовкою фахівців технічних спеціальностей у вітчизняних вищих навчальних закладах. Пропонуються шляхи вирішення завдань підвищення якості підготовки інженерів та керівників для народногосподарського комплексу міста, області, країни в цілому на прикладі досвіду Харківської національної академії міського господарства.

In article the questions connected with preparation of experts of technical specialities in domestic higher educational institutions are considered. Ways of the operative decision of problems on improvement of quality of preparation of engineers and heads for an economic complex of a city, area, the country as a whole on an example of modern experience of the Kharkov national academy of municipal economy are offered.
New practice of preparation of experts of technical specialities in the higher school: experience of the Kharkov region
Keywords: безперервна освіта; вища освіта України; рівні компетенції; мережні структури; наука